The world to come [videorecording (DVD)] - Waterston, Katherine; Kirby, Vanessa; Abbott, Christopher, 1986-; Affleck, Casey, 1975-; Gherasim, Karina Ziana (Wolfe, 2021)
Somewhere along the mid-nineteenth century American East Coast frontier, two neighboring couples battle hardship and isolation, witnessed by a splendid yet testing landscape, challenging them both physically and psychologically.